Stories About Old Age in Times of the Transition Process - Đurić Paunović, Ivana V.; Stevanović, Kristina I. (Collection of Papers of the Faculty of Philosophy in Priština, 2019)
The period of transition in post-Yugoslav countries has left its mark on various cultural and artistic practices, with tropes and themes indicating the changes and turns in the perception of reality. One of the aspects of rendering of reality in literature relates to old age, as one of the less frequently covered topics, albeit important for understanding the consequences of the times. Drawing on the findings of age studies, the paper discusses the elements of representation of old age and aging in Serbian short stories that deal with this period. The literary analyses of the selected stories by D. Albahari, Lj. Đurđić, V. Marković, G. Petrović, and M. Vujičić, have shown that although some of the stereotypical traits in depiction of old age are still present, the authors have, by following the lives of their protagonists in turbulent times, offered a rendering of old people who do not have the opportunity to settle into a routine of quiet life (which is probably expected to happen due to their age), but rather struggle to find some sense in times of confusion. The juxtaposition of old and young does not put the two groups at opposite poles – in the stories they create a mutual support system, sometimes even unintentionally. The paper covers the topics of male and female aging; of chronological and biological age; of cultural constructs supporting the stereotypes in contemporary Serbian short prose.